Avaliação da qualidade de artefatos em linhas de processo de software adaptada - Brondani, Camila Hübner (2016)
In software engineering, it is necessary to consider indicators related to quality, such as: effort, productivity, time and cost of development in order to achieve an effective project control. These indicators are negatively affected when defective artifacts are produced. In this case, the cost of rework to correct defects increases in relation to the time of their discovery. Therefore, initiatives should be conducted in order to find these defects and correct them as soon as they are introduced. There are different norms and models designed to ensure and continuously improve the quality of software. Among these, the CMMI (Capability Maturity Model Integration) is a reference model that contains best practices for development and maintenance of products, with a focused approach to the maturity of software processes. In addition to the software process to be effective in a particular project it is necessary that it considers the peculiarities of the project in focus. Therefore, quality assessment process models propose that organizational processes are tailored to the needs of a particular project and is created as a result of the specific process for this. Thus, this paper presents an approach for assessing the quality of artifacts generated and/or transformed by the several activities that have a software process defined using Software Process Lines (SPrL). The activities of the tailored process are selected to satisfy the practices of the quality model CMMI. This proposal is supported by a quality framework, consisting of a metamodel, a knowledge base developed from the CMMI, an evaluation process and a support tool. The framework incorporates principles of quality models for the evaluation of software products and has as main objective the instantiation of a plan to evaluate the quality of software artifacts. Finally, the proposal was evaluated and validated through real case studies of different companies and involved five professionals with relevant experience in software development. So it was generated five tailored processes according to the context of the projects and as the CMMI practices selected, in addition to the development of quality plans for evaluation of the artifacts generated by the activities of the process. The experts analyzed the approach and considered positively the proposal of this work.